Social and medical aspects of undescended testes in Turkey - (:unkn) unknown (Elsevier B.V., 1995)
In this study, 6,381 primary school boys were examined in Turkey in the years 1990 and 1991 and families and medical personnel were questioned about the information they had on undescended testes and their behavior regarding this matter was noted. Undescended testes were found in 91/6,381 pupils (1.43%). Forty-six families (58.7%) were aware of the abnormality. In 36 of these 46 cases (78%), the mother was the first who noticed the problem. Only 3 cases were first diagnosed by medical staff (nurses or doctors). Eighteen cases were diagnosed under 2 years of age, but apparently they had not been managed correctly because of ignorance regarding possible complications. Of the 46 families, who were aware of the problem, only 29 (63%) had seen a physician. In other words, only 31% (29/91) of the boys with undescended testes received medical help. This study has shown that no genital organ examination of the newborn is performed after most deliveries and there is a considerable unawareness of undescended testes both by the families and by medical personnel.
Keywords: Congenital anomaly; Orchipexy; Pediatric urology; Undescended testis